About international cooperation of researchers of catholic church and it‘s result. - Streikus, Arūnas (Genocidas ir rezistencija, 2002)
On 12–13 October 2001, Riga hosted the Baltic Church Historians’ Seminar for the second time (the first meeting took place in 2000 in Tartu). The seminar was attended by scholars from Estonia, Latvia, Lithuania, Finland, and Sweden. The meeting did not focus solely on specific problems in the Church’s history, but rather on exchanging information on the state of research, networking and discussing joint research projects. There are not yet enough historians in all the Baltic states who would focus their research exclusively on the Church’s experience under the totalitarian dictatorships. For obvious reasons, the hosts of this conference, the Latvians, were the most represented, but it is fair to say that among the four participants from Latvia who presented four papers, there was not a single professional in the field.
Keywords: Catholic Church; Baltic countries; historical researches